2010
DOI: 10.1007/s00192-010-1149-6
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy- and delivery-induced biomechanical changes in rat vagina persist postpartum

Abstract: Introduction and hypothesis-We sought to define changes in vaginal distensibility (VD) induced by pregnancy and vaginal delivery using a novel in vivo biomechanical testing protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 10 publications
5
36
0
Order By: Relevance
“…These findings are in agreement with studies in mice [25] and rats [26] where the supportive perivaginal tissues decreased in stiffness and strength during pregnancy and returned to virgin levels four weeks after delivery [26]. However, another rat study showed increased vaginal distensibility during pregnancy compared to virgins, which did not return to virgin levels four weeks postpartum [27]. We also found a higher level of induced permanent strain following cyclic loading in pregnant vaginal tissue, indicating it was the least elastic by this measure and the least likely to return to its original dimensions.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in agreement with studies in mice [25] and rats [26] where the supportive perivaginal tissues decreased in stiffness and strength during pregnancy and returned to virgin levels four weeks after delivery [26]. However, another rat study showed increased vaginal distensibility during pregnancy compared to virgins, which did not return to virgin levels four weeks postpartum [27]. We also found a higher level of induced permanent strain following cyclic loading in pregnant vaginal tissue, indicating it was the least elastic by this measure and the least likely to return to its original dimensions.…”
Section: Discussionsupporting
confidence: 90%
“…26 Rat has also been shown to be a reliable model for the study of pregnancy-related changes in cervix, vagina, and vaginal supportive structures. 14,27,28 In this study we quantified the structural adaptations that take place in the PFMs throughout pregnancy and determined the extent of recovery after vaginal delivery. Second, to determine whether these changes are specific to the PFMs or occur throughout the body, we examined a hind limb muscle, the tibialis anterior.…”
mentioning
confidence: 99%
“…We recognize that the difference in posture and small fetal size of the species we evaluated makes naturally occurring PFD a rare event in these animals. However, a rodent model has been a reliable exemplar for the study of pregnancy adaptations and effects of simulated birth injury [28, 29]. Pregnancy-induced adaptations in rat persist postpartum [29]; also, simulated birth injury in rodent induces stress urinary incontinence via injury of striated muscles [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, a rodent model has been a reliable exemplar for the study of pregnancy adaptations and effects of simulated birth injury [28, 29]. Pregnancy-induced adaptations in rat persist postpartum [29]; also, simulated birth injury in rodent induces stress urinary incontinence via injury of striated muscles [30]. Despite the limitations listed above, our study provides prerequisite data on the structure of the pelvic skeletal muscle in mouse, rat, and rabbit, all of which are frequently used for studying PFD.…”
Section: Discussionmentioning
confidence: 99%